What is crisis migration? - Susan Martin; Sanjula Weerasinghe; Abbie Taylor (Forced Migration Review, 2014)
Movements precipitated by humanitarian crises have implications that touch upon immigration control and national interests, human rights, humanitarian and development principles, and the frameworks for international protection, cooperation and burden sharing. Existing legal and institutional frameworks manifest limited capacity to accommodate all those with protection needs. Even when frameworks exist, in practice there are considerable gaps in implementation.